2006
DOI: 10.1111/j.1365-2591.2006.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of sodium hypochlorite and chlorhexidine against selected single‐species biofilms

Abstract: Mechanical agitation improved the antimicrobial properties of the chemical substances tested using a biofilm model, favouring the agents in liquid presentation, especially 5.25% NaOCl and 2% chlorhexidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
2
38

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(170 citation statements)
references
References 51 publications
5
125
2
38
Order By: Relevance
“…The 2.5% NaOCl group and 2% CHX group's CFU counts had no statistically significant difference, which suggests that 2% CHXs antifungal properties are comparable to 2.5% NaOCl's antifungal properties against the C. albicans biofilm. Sena et al found similar result that both NaOCl and CHX have antifungal properties but do not differ significantly, supporting the findings of this study [15].…”
Section: Discussionsupporting
confidence: 81%
“…The 2.5% NaOCl group and 2% CHX group's CFU counts had no statistically significant difference, which suggests that 2% CHXs antifungal properties are comparable to 2.5% NaOCl's antifungal properties against the C. albicans biofilm. Sena et al found similar result that both NaOCl and CHX have antifungal properties but do not differ significantly, supporting the findings of this study [15].…”
Section: Discussionsupporting
confidence: 81%
“…It is by far the fungal species most commonly isolated from in- www.bjournal.com.br fected root canals, showing resistance to intracanal medication (3). The ability to form a biofilm and to invade dentinal tubules may help to explain the association with cases of persistent root canal infections (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…This is a result of the physical limitations of endodontic instruments and the short time irrigants remain in the root canal during instrumentation/ irrigation procedures. Although sodium hypochlorite (NaOCl) has excellent antimicrobial activity against most putative endodontic pathogens (5), this irrigant is allowed to act within the root canal system only for a short period. As chemomechanical preparation procedures have been expedited after introduction of rotary instruments, the permanence of NaOCl within the root canal has been even shortened.…”
Section: Introductionmentioning
confidence: 99%